New electronic memory device concepts based on metal oxide-polymer nanostructures planer diodes - Kiazadeh, Asal (2014)
Nanostructure silver oxide thin films diodes can exhibit resistive switching effects. After an electroforming process the device can be programmed between a low conductance (off-state) and high conductance (on- state) with a voltage pulse and they are already being considered for non-volatile memory applications. However, the origin of programmable resistivity changes in a network of nanostructure silver oxide embedded in polymer is still a matter of debate. This work provides some results on a planer diode which may help to elucidate resistive switching phenomena in nanostructure metal oxide diodes. The XRD pattern after switching appears with different crystalline planes, plus temperature dependent studies reveal that conduction of both on and off states is weak thermal activated. Intriguing the carrier transport is the same for both on and off-states. Difference between states comes from the dramatic changes in the carrier density. The main mechanism of charge transport for on-state is tunneling. The charge transport leads to SCLC in higher voltages pulse for the off state. The mechanism will be explained based on percolation concepts.